Use of equipment neuroscientists to corroboration meanings. - A. París, José (Revista Universidad de Guayaquil, 2011)
Marketing specialists around the world have rushed to define the current of “neuromarketing”, we do not agree that it is a new paradigm of marketing. In fact for us neuroscience is another disciplines based on what we call “essential latinomerican marketing”, as are other disciplines and sciences such as sociology, semiology, psychology and anthropology. For that, this article presents the application of the experimental technique of electroencephalography mobile which is very useful to corroborate the meanings interpreted by our techniques from outcrops of meanings.